Composition and Evaluation of a Medicinal Herbal Shampoo Based on Ziziphus spina-christi, Olive Oil, and Potassium Hydroxide - Noora B. Maizar; Ali .F. Al-Qaisi; Nada A.Alshemari; Aya H.Khader; Noor Alhuda S. Najem; Anfal S.Abdul Razzaq; Ahmed F. Alobaidi; Rakhaa S. Alnassralla (Health & Medical Sciences, 2026)
This study aimed to formulate and evaluate a medicinal herbal shampoo based on Ziziphus spina-christi leaves, olive oil, and potassium hydroxide (KOH). Z. spina-christi is rich in saponins, providing natural cleansing, anti-dandruff, and soothing effects, while olive oil contributes hydration and protection for hair. KOH was used to saponify the oil, producing a mild liquid potassium soap suitable for scalp application.The optimized formulation contained 15% olive oil, stoichiometrically calculated KOH, and 3% finely powdered Z. spina-christi extract, diluted with distilled water. Natural preservatives were included to enhance stability, and the pH was adjusted to 6.0, ensuring optimal scalp compatibility.Evaluation included physicochemical characterization (pH, viscosity, appearance), microbial stability (total microbial count over 1–3 months), and dermatological safety (patch test). Preliminary anti-dandruff efficacy was also assessed. The shampoo demonstrated mild cleansing, moderate foaming, moisturizing, and soothing properties, while remaining free from synthetic surfactants . This work presents a scientifically validated herbal shampoo integrating traditional plant-based remedies with modern formulation principles, offering a safe, effective, and natural alternative for hair care. The findings support the potential of Z. spina-christi and olive oil as key ingredients in herbal medicated shampoos with enhanced anti-dandruff and hair-conditioning performance.